Telaah Q.S. Al-Baqarah Ayat 222 Tentang Kesehatan Dan Kebersihan - Naysila Putri Aulia; Suci Shintya Sari; Dwiky Kurniawan Saragih (Yayasan Bayt Shufiya Nusantara, 2025)
Health and cleanliness are two essential aspects of human life that receive significant attention in Islamic teachings. This study aims to explore the meaning and message contained in Surah Al-Baqarah verse 222, particularly in relation to marital relations, personal purity, and the dimensions of cleanliness from both spiritual and physical perspectives. The research employs a literature review method using a thematic (maudhu’i) tafsir approach by examining interpretations from classical and contemporary scholars. The findings reveal that the verse not only prohibits sexual relations during menstruation as a form of biological protection but also conveys moral and educational messages regarding respect for women, the strengthening of family relationships, and the instilling of cleanliness as an expression of obedience to God. In addition to its physical health benefits, Islamic cleanliness practices align with modern health principles and contribute to psychological balance and spiritual resilience. Thus, cleanliness in Islam is not merely a ritual obligation but a fundamental ethical and social principle for building a healthy, harmonious, and sustainable life.